[Kapit sa patalim ; In search of a father ; Kuro-kuro ng isang kompositor [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Tackles on Philippine economic problem during Pres. Aquino's administration; Amerasian children in search for their father and their social conditions; and, Gary Granada's songs and his interpretations on each composition.
Kapit sa patalim (14 mins.) -- In search of a father (17 mins.) -- Kuro-kuro ng isang kompositor (19 mins.)
VHS.
Keywords: Granada, Gary; Strikes and lockouts -- Philippines; Abandoned children -- Philippines; Amerasians -- Social conditions. -- Philippines; Composers, Filipino; Orphans -- Philippines; Philippines -- Economic conditions; Philippines -- Social conditions